2021
DOI: 10.1371/journal.pcbi.1008013
|View full text |Cite
|
Sign up to set email alerts
|

Linear-nonlinear cascades capture synaptic dynamics

Abstract: Short-term synaptic dynamics differ markedly across connections and strongly regulate how action potentials communicate information. To model the range of synaptic dynamics observed in experiments, we have developed a flexible mathematical framework based on a linear-nonlinear operation. This model can capture various experimentally observed features of synaptic dynamics and different types of heteroskedasticity. Despite its conceptual simplicity, we show that it is more adaptable than previous models. Combine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…A wrong short-term plasticity model will therefore lead to a wrong connectivity in the circuit. Here, it will be interesting to see how a more expressive model of short-term plasticity [ 70 ] influences the optimal circuit structure. Finally, of course, our optimality assumption could be wrong to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…A wrong short-term plasticity model will therefore lead to a wrong connectivity in the circuit. Here, it will be interesting to see how a more expressive model of short-term plasticity [ 70 ] influences the optimal circuit structure. Finally, of course, our optimality assumption could be wrong to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these factors influence the interaction between the pre- and postsynaptic neurons which cannot be captured by the dynamics of STP solely. It was suggested that alternative models of plasticity with less biophysical constraints like generalized bilinear model [ 15 ] and linear-nonlinear cascade model [ 19 ] could provide more flexible representation of STP dynamics compared to the TM model. Despite such limitations, the conventional three-parameter TM model is sufficient to describe STP in many cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ghanbari et al [ 15 , 18 ] also used a different GLM to directly estimate the STP dynamics, a model that can be considered as an alternative to the TM model. Rossbroich et al [ 19 ] introduced a new synaptic model which represents short-term dynamics by combining an exponential kernel with a non-linear readout function. The simplicity of this model enabled applying the concepts of STP in artificial neural networks to examine its role in learning.…”
Section: Introductionmentioning
confidence: 99%
“…These connections all show STF with frequency dependence (Milstein et al, 2015;Wierenga et al, 2005) arising from multi-vesicular release (Soares et al, 2019;Dürst et al, 2022). This suggests a preponderance of STF for inputs onto CA1, a trend that extends to other parts of the hippocampus (Salin et al, 1996;Toth et al, 2000;Rossbroich et al, 2021). CA1 pyramidal neurons then project to multiple targets, with many connections going to the subiculum.…”
Section: Differential Transmission Of Firing Patternsmentioning
confidence: 97%